EPV 13. Pain-related evoked potentials depict the effect of conditioned pain modulation in healthy subjects. Issue 9 (September 2016) - Höffken, O.; Özgül, Î.; Enax-Krumova, E.; Tegenthoff, M.; Maier, C.
Abstract : Background: Conditioned pain modulation (CPM) evaluates the pain modulating effect of a noxious conditioning stimulus (CS) on another noxious test stimulus (TS), mostly based on subjective pain ratings (Yarnitsky et al., 2015 ). We now use electrical stimulation (TS) of intraepidermal nerve fibres, reflecting the nociceptive A δ -fibre transmission (Katsarava et al., 2006 ), to investigate whether cortically recorded pain-related evoked potentials (PREP) can depict the CPM-effect. Methods: We examined 17 healthy subjects using a novel CPM-protocol. We recorded PREP (including the assessment of the PREP-induced pain) over Cz referred to linked ear lobes, stimulating the dominant hand with the two-fold of the individual pain threshold (2PT) using three custom-built concentric surface electrodes. We than evaluated the CPM-effect in a cross-over design with immersion of the non-dominant hand into either 10 °C or 24 °C (control) cold water as CS. As TS we recorded PREP stimulating with pain intensity of 40–60 on the NRS 0–100 before, and repeatedly during and after CS application. Statistics: Pearson correlation, ANOVA, paired t -test, linear regression. Result: At 2PT the PREP-induced pain and PREP-amplitude did not correlate. With increasing stimulus intensity from 2.3  ±  0.3 mN to 6.7  ±  1.4 mN, the PREP-induced pain raised from 24.5  ±  3.8 to 52.1  ±  1.1 ( p  < 0.001), while the PREP-amplitude remained unchained. Only in the 10 °C-condition, both PREP-induced pain intensity (52.6  ±  4.4 vs. 30.3  ±  12.5) and PREP-amplitude (42.1  ±  13.4  μ V vs. 28.7  ±  10.5  μ V) decreased during and increased after CS termination (all p   <  0.001). The changes of PREP-induced pain and PREP-amplitudes correlated only in the 10 °C-condition ( r  = 0.5; p  = 0.042). Discussion: The presented novel CPM-protocol with hand immersion in painful cold water as conditioning stimulus can be used to modulate the PREP-induced pain intensity in healthy subjects and, more importantly, the PREP-recordings are able to depict quantitatively the CPM-effect electrophysiologically in an objective way.